Studi Cross-Textual Reading Terhadap Kisah Padi Pulut dan Kisah Elia dan Janda di Sarfat - Jefri Andri Saputra; Mordekai Mordekai (Jurnal Abdiel: Khazanah Pemikiran Teologi, Pendidikan Agama Kristen dan Musik Gereja, 2023)
This study aims to provide an alternative regarding the attitude that the church should have in dealing with crises. The crisis referred to here refers to an economic recession. Following up on this effort, the author examines the story "The Origin of Sticky Rice" with the Story of Elijah and the Widow in Sarfat according to the text of 1 King 16:29-17:24, using a cross-textual reading approach. Based on the analysis, the writer finds that a crisis is not a reason not to share. Instead, God perpetuates its maintenance through human faith and obedience to Him and by way of acceptance, hospitality, and sharing with others.